2018
DOI: 10.3389/fped.2018.00313
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Dynamics of the Milk Fat Globule and Its Role in Infant Development

Abstract: Human milk is uniquely optimized for the needs of the developing infant. Its composition is complex and dynamic, driven primarily by maternal genetics, and to a lesser extent by diet and environment. One important component that is gaining attention is the milk fat globule (MFG). The MFG is composed of a triglyceride-rich core surrounded by a tri-layer membrane, also known as the milk fat globule membrane (MFGM) that originates from mammary gland epithelia. The MFGM is enriched with glycerophospholipids, sphin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
223
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(229 citation statements)
references
References 231 publications
(315 reference statements)
2
223
1
3
Order By: Relevance
“…Evolutionary pressures have designed milk to be an excellent source of macronutrients and micronutrients for the growing infant, which provides it with some unique features (Bourlieu et al., ; Le Huerou‐Luron, Lemaire, & Blat, ; Lee et al., ). The milk fat globule membrane (MFGM) in raw bovine milk contains components (lipids, proteins, and carbohydrates) that are believed to interact with the gut microbiome of the growing infant (Bourlieu et al., ).…”
Section: Gastrointestinal Fatementioning
confidence: 99%
“…Evolutionary pressures have designed milk to be an excellent source of macronutrients and micronutrients for the growing infant, which provides it with some unique features (Bourlieu et al., ; Le Huerou‐Luron, Lemaire, & Blat, ; Lee et al., ). The milk fat globule membrane (MFGM) in raw bovine milk contains components (lipids, proteins, and carbohydrates) that are believed to interact with the gut microbiome of the growing infant (Bourlieu et al., ).…”
Section: Gastrointestinal Fatementioning
confidence: 99%
“…Several randomized clinical trials (RCTs) have also shown that infants supplemented with DHA show better language and communication skills [30,31]. On the other hand, research efforts have focused on infant formula supplementation with MFGM, which is a biologically active component derived of milk proteins present in human milk [32], including a lipid fraction consisting of LC-PUFAs (also ARA and DHA) [33]. In this regard, addition of MFGM to an infant formula has been found to improve immune system and neurodevelopment during the first months of life [8,34].…”
Section: Discussionmentioning
confidence: 99%
“…As major components of the milk lipid droplet (LD) membrane for lipid secretion, butyrophilin 1a1 (BTN, encoded by the Btn1a1 gene) is important for milk lipid secretion and therefore neonatal survival 13,15,16 . Xanthine oxidoreductase (XOR, encoded by the Xdh gene) is also reported to modulate milk lipid secretion during lactation [17][18][19] . However, although some studies have found that XOR can be regulated by various factors at the transcriptional level [20][21][22] , little attention has been paid to post-transcriptional regulators.…”
mentioning
confidence: 99%